Visibilidade mediática, identidade e imaginário infantil na cibercultura: as múltiplas identidades da criança em plataforma virtuais de relacionamento - Folino Junior, Ariovaldo (2014)
The object of this research is the subjective manifestations and changes in the identity and imagination of children who access cybercultural communication and relationship platforms. The content of the corpus encompasses profiles and avatars of 6 to 12-year-old users in simulation environments, specifically Penguin Club, Dragon City and CityVille. The research objective is to understand the intrinsic relationship between subjectivity and media visibility, considering the transformations of the child s identity and imagination in face of the hyper-spectacle of the dissolution of the individual in social networks. The main problem translates into two questions: (a) how to see the development of the child s self in its avatars, with its multiple identities in relationship platforms; and (b) how the child s imaginary is articulated in this context. Accordingly, the search process is guided by the following hypotheses: (a) the ongoing construction of profiles requires various identities, resignifying the very self of the child; (b) the projection of its real self in the network transforms its constitution into verbal/imagistic production, which dereferences its identity; and (c) this conjuncture leads to a reconfiguration of the child s imaginary. The methodology included a literature review and observation of behavior in virtual environments according to netnography, based on which, by means of noninvasive admission to the cited platforms, an exploratory analysis of profiles and avatars was performed. The theoretical framework of reference was based on theoretical postmodernism (ANDERSON; BAUDRILLARD; HARVEY; LYOTARD), on the concepts of cyberculture (LEMOS; TRIVINHO), and on reflections about the formation of identity (BAUMAN; GIDDENS; HALL; LIPOVETSKY; CHARLES), of childhood and of the imaginary (CASTORIADIS; FELINTO; TRIVINHO)